Skin shade and relationships: how colourism pits Black and mixed Black-White women against each other - Phoenix, Aisha; Craddock, Nadia (Frontiers in Sociology, 2024)
IntroductionColourism, prejudice where people are penalised the darker their skin and the further their features are from those associated with whiteness, occurs within and between racialised groups and can affect relationships. In this paper we examine the complex processes through which colourism positions Black and mixed Black-White women in contrasting positions in beauty and desirability hierarchies based on their skin shade.MethodSemi-structured interviews were conducted with 27 Black (n = 18) or mixed Black-White (n = 9) adults (18 women, 9 men) living in Britain. Data were analysed using reflexive thematic analysis.ResultsAnalysis generated four main themes. First, colourist and gendered appearance ideals promoted by mainstream media serve to devalue and thus harm Black people, particularly Black women with dark skin. Second, these ideals can affect Black and mixed Black-White women’s experiences of the heterosexual relationship market where women with light skin are desired and those with darker skin often overlooked. Third, colourist appearance ideals and colourist-induced inequities in the heterosexual relationship market affect relationships between Black and mixed Black-White women of different skin shades. Fourth, fostering Black self-acceptance, celebrating natural Black beauty, and creating spaces for dialogue between women of different skin shades are seen as ways to address some aspects of colourism and/or their affects.DiscussionFindings highlight how colourism shapes desirability in gendered ways and how this affects the lives of Black and mixed Black-White women, influencing within-group social dynamics and relationships.